(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
This study explores preventive strategies for pneumonia with broncho-obstructive syndrome in children under three in the Fergana Region. By analyzing clinical data and international guidelines, it highlights key interventions—such as vaccination, improved nutrition, environmental modifications, and early detection—that reduce the incidence and severity of this condition. The research underscores the importance of integrated approaches addressing both infectious and obstructive factors, offering practical recommendations for early prevention in high-risk pediatric groups.